Syntheses of dibenzo[d,d']benzo[2,1-b:3,4-b']difuran derivatives and their application to organic field-effect transistors - Truong, Minh Anh; Nakano, Koji (Beilstein Journal of Organic Chemistry, 2016)
Ladder-type π-conjugated compounds containing a benzo[2,1-b:3,4-b']difuran skeleton, such as dibenzo[d,d']benzo[2,1-b:3,4-b']difuran (syn-DBBDF) and dinaphtho[2,3-d:2',3'-d']benzo[2,1-b:3,4-b']difuran (syn-DNBDF) were synthesized. Their photophysical and electrochemical properties were revealed by UV–vis absorption and photoluminescence spectroscopy and cyclic voltammetry. Organic field-effect transistors (OFETs) were fabricated with these compounds as organic semiconductors, and their semiconducting properties were evaluated. OFETs with syn-DBBDF and syn-DNBDF showed typical p-type characteristics with hole mobilities of <1.5 × 10−3 cm2·V−1·s−1 and <1.0 × 10−1 cm2·V−1·s−1, respectively.
Keywords: furan; heteroacenes; organic field-effect transistors; organic semiconductor